Frontier and Future Development of Information Technology in Medicine and Education ITME 2013 - Li, Shaozi; Jin, Qun.; Jiang, Xiaohong; Park, James J. (Jong Hyuk).; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
IT changes everyday$1 (Bs life, especially in education and medicine. The goal of ITME 2013 is to further explore the theoretical and practical issues of IT in education and medicine. It also aims to foster new ideas and collaboration between researchers and practitioners.s
The anti-apoptotic effect of transgenic Akt1 gene on cultured new-born rats cardiomyocytes mediated by ultrasound/microbubbles destruction -- Logic Operation in Spiking Neural P System with Chain Structure -- A Mathematical Model of the Knee Joint for Estimation of Forces and Torques during Standing-up -- Adaptive Online Learning Environment for Life-Long Learning -- A Membrane Bin-Packing Technique for Heart Disease Cluster Analysis -- Chap. Teaching Chinese as a Foreign Language Based on Tone Labeling in the Corpus and Multi-model Corpus -- A systematically statistical analysis of effects of Chinese Traditional Setting-up Exercise on healthy undergraduate students -- Sample-independent Expression Stability Analysis of Human Housekeeping Genes Using the GeNORM Algorithm -- Development of A One-step Immunochromatographic Strip Test for Rapid Detection of Antibodies against classic swine fever -- Cramer-Von Mises statistics for testing the equality of two distributions.
Keywords: Engineering; Medical records -- Data processing; Education; Telecommunication; Engineering; Communications Engineering, Networks; Health Informatics; Computers and Education